Theoretical Study on Impact of Solar Radiation Heat Gain on Thermal Comfort and Energy Efficiency in Glass Curtain Wall Buildings Based on PMV Index - Haoyu Chen; Jinzhe Nie; Yuzhe Liu; Yuelin Li (Buildings, 2025)
With rapid global urbanization, glass curtain wall buildings have been widely adopted due to aesthetics and natural lighting. However, during summer time, intense solar radiation leads to significant indoor heat gain, which adversely affect thermal comfort and energy efficiency. The conventional air conditioning systems are typically equipped with a cooling capacity sufficient to maintain an indoor air temperature at the design values specified in the Design standard for energy efficiency of public buildings, which fails to account for the effects of radiation temperature, potentially resulting in reduced thermal comfort and energy inefficiency. By integrating the Thermal Comfort Tool to calculate the PMV index, this study evaluates the affection of solar heat gain on indoor occupants’ thermal comfort and proposes an optimized air temperature control strategy to realize thermal comfort. Based on the dynamic air temperature strategy, an energy consumption model is developed to evaluate the affection of solar radiation on energy consumption for glass curtain wall buildings based on the PMV index. The synergistic effects of shading measures are then evaluated. This study conducts simulation analysis using an office building with a glass curtain wall located in Beijing as a case study. When accounting for radiant heat gain, a significant portion of the time (53.89%) fall outside the thermal comfort range, even when the air conditioning is set to the designated temperature. To maintain thermal comfort, the air conditioning temperature must be lowered by 1.4–3.5 °C, resulting in a 28.08% increase in energy consumption. To address this issue, this study finds that installing interior shading can reduce radiant heat gain. Under the same thermal comfort conditions, the required air temperature reduction is only 0.8–2.1 °C, leading to a 24.26% reduction in energy consumption compared to the case without interior shading.